STRATEGI PENERIMAAN PESERTA DIDIK BARU DI ERA GEN-Z PADA SMK PGRI 1 NGAWI: 10.56997/inisiasi.v4i2.1952 - sukmawati, affrilya; zhubaidah, thika; Tyas, Zuhriana Widya Rahayu Ning (Institut Agama Islam Ngawi, 2025)
Admission of New Students (PPDB) is a very important thing in an educational institution. The promotional strategy they offer is different from other schools. Grisa holds workshops/training so it's not just promotion or distributing brochures for each department, releasing superior programs and making video content. What's interesting is to introduce each department. This is very effective in attracting junior high school students in the current Gen-Z era. From year to year, PPDB Grisa always has breakthroughs in innovation that are increasingly interesting through social media content resulting from the work of creative student council students. The full Grisa PPDB route is online for all banners that are installed, there is a QR code that can be scanned or a direct link. Not only that, Grisa also has many flagship programs. Grisa has a vision and mission to produce graduates who have competitiveness and are able to compete nationally and internationally.